A broadband all-fiber integrated graphene photodetector with CNT-enhanced responsivity. Issue 26 (30th June 2020) - Zhuo, Linqing; Fan, Pengpeng; Zhang, Shuang; Liu, Xiaohe; Guo, Xinyi; Zhang, Yu; Zhan, Yuansong; Li, Dongquan; Che, Zhen; Zhu, Wenguo; Zheng, Huadan; Tang, Jieyuan; et al.
Abstract : We achieve a broadband and ultrahigh responsivity all-fiber photodetector by integrating hybrid CNT/graphene films on a side-polished fiber (SPF). Abstract : Carbon-based nanomaterials such as carbon nanotubes (CNTs) and graphene have great potential for high-performance all-carbon photodetectors due to their unique optical and electronic properties. Here, we assemble a hybrid CNT/graphene film prepared by depositing CNTs on a single layer graphene with a side-polished optical fiber to achieve a novel all-fiber integrated photodetector. Because CNTs strongly enhanced the interaction between graphene and the fiber mode, the photodetector shows an extra-high photoresponsivity over the visible and infrared region. Especially at 1550 nm, the photoresponsivity is found to be ∼1.48 × 10 5 A W −1, which is 6.5 times larger than those of photodetectors without CNTs. These findings provide a highly versatile, reproducible, and low-cost platform to integrate novel zero-, one-, and two-dimensional materials into optical fibers and deliver more sophisticated functionalities.